A Cytokine-Centric View of the Pathogenesis and Treatment of Autoimmune Arthritis - Astry, Brian (Mary Ann Liebert, Inc., 2011)
Cytokines are immune mediators that play an important role in the pathogenesis of rheumatoid arthritis (RA), an autoimmune disease that targets the synovial joints. The cytokine environment in the peripheral lymphoid tissues and the target organ (the joint) has a strong influence on the outcome of the initial events that trigger autoimmune inflammation. In susceptible individuals, these events drive inflammation and tissue damage in the joints. However, in resistant individuals, the inflammatory events are controlled effectively with minimal or no overt signs of arthritis. Animal models of human RA have permitted comprehensive investigations into the role of cytokines in the initiation, progression, and recovery phases of autoimmune arthritis. The discovery of interleukin-17 (IL-17) and its association with inflammation and autoimmune pathology has reshaped our viewpoint regarding the pathogenesis of arthritis, which previously was based on a simplistic T helper 1 (Th1)-Th2 paradigm. This review discusses the role of the newer cytokines, particularly those associated with the IL-17/IL-23 axis in arthritis. Also presented herein is the emerging information on IL-32, IL-33, and IL-35. Ongoing studies examining the role of the newer cytokines in the disease process would improve understanding of RA as well as the development of novel cytokine inhibitors that might be more efficacious than the currently available options.